Determinants that affecting exchange rate in Malaysia / Sabirin Saleh - Saleh, Sabirin (Faculty of Business and Management, 2018)
This study will focus on the determinants that affecting exchange rate in Malaysia. The objective of this study is to examine the relationship between Inflation Rate, Money Supply, Gross Domestic Product and Foreign Direct Investment towards Exchange Rate in Malaysia. In order to achieve the objective, this study applies the Autoregressive distributed lag model and used annually data over the period 1975 until 2015 from authorized sources. The study revealed that in ARDL Model there is a significant positive and insignificant positive relationship between Exchange rate and the selected determinants which is Inflation Rate and Money Supply respectively. Meanwhile, Gross Domestic Product and Foreign Direct Investment are found negative but significant towards Exchange Rate. This study is important for the government to retain tight monetary and fiscal policies in order to stable exchange rate in the Malaysia. Besides that, central bank will also get benefits in order to promote monetary authorities at managing exchange rate effectively.